2012
DOI: 10.1007/s10853-012-6433-z
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and mechanical behaviour of flexible polyurethane foams modified with graphite and phosphorous fillers

Abstract: Flexible polyurethane foams (FPF) are polymer materials that have high flammability. Fyrol PNX (FPNX) and expandable graphite (EG), have been used to modify the properties of these materials. The aim of this study was to assess the possibility of improving the thermal stability and flame retardancy of FPF by the addition of FPNX and EG fillers. The prepared foams were characterised by their apparent density, hardness, flexibility, irreversible strain and linear flammability, as well as thermogravimetric analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(46 citation statements)
references
References 32 publications
(55 reference statements)
2
44
0
Order By: Relevance
“…A common technique for retarding the flammability of PUF is to introduce bromine-based molecules that scavenge (H • and OH • ) radicals in the gas phase [5,6], but these halogenated additives are undergoing worldwide scrutiny for the toxic smoke they release and their potential to leach into the environment [7][8][9]. Platelet-based and intumescent nanocoatings have been developed in recent years to address these issues [10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…A common technique for retarding the flammability of PUF is to introduce bromine-based molecules that scavenge (H • and OH • ) radicals in the gas phase [5,6], but these halogenated additives are undergoing worldwide scrutiny for the toxic smoke they release and their potential to leach into the environment [7][8][9]. Platelet-based and intumescent nanocoatings have been developed in recent years to address these issues [10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The decomposition of developed PUF F was performed in the temperature range from 30 o C-800 o C. The thermal stability was assayed at 5 % and 50 % weight loss of PUF F samples. 5 % and 50 % weight loss corresponds to the initial and soft segments decomposition respectively [24]. …”
Section: Thermogr Avi Metric Analysis (Tga) -Thermal Characteristics mentioning
confidence: 99%
“…They indicated that the thermal stability and fire resistance of high-density polyethylene/ethylene vinyl-acetate blend were enhanced significantly by EG and improved with decreasing particle size of EG. Besides, the possibility of improving the thermal stability and flame retardancy of flexible polyurethane foams by the addition of expandable graphite fillers has been assessed by Wolska et al [20], and it revealed the modification by the addition of expandable graphite was an effective way to improve the thermal stability of flexible polyurethane foam.…”
Section: Introductionmentioning
confidence: 99%